Photocontrolled molecular structural transition and doping in graphene - Peimyoo, Namphung (2013)
We studied chemical doping of trans- and cis-azobenzene on graphene by Raman spectroscopy. It was found that the molecule induces hole-doping in graphene through charge transfer. Moreover, the doping level in graphene can be reversibly modulated by a photocontrolled molecular conformation change. As trans-azobenzene isomerizes to the cis configuration under UV irradiation, we probe the dynamic molecular structural evolution of azobenzene on graphene by Raman spectroscopy. Raman analysis indicates the precise orientation of cis-azobenzene on the graphene surface, which brings us further comprehension of the effect of conformation change on the electronic properties of graphene. In particular, the substantial decreases of the doping level and chemical enhancement of the molecular signal are attributed to the weakening of hole transfer from molecule to graphene, owing to the lifting of the electron-withdrawing group away from the graphene. Moreover, the calculation results exhibit the favorable configuration of cis-azobenzene, which is in good agreement with Raman spectroscopic analysis. Our results highlight an approach for employing graphene as a promising platform for probing molecular conformation transition at the submolecular level by Raman spectroscopy.